Sequencing HIV-neutralizing antibody exons and introns reveals detailed aspects of lineage maturation. Issue 1 (December 2018) - Johnson, Erik; Doria-Rose, Nicole; Gorman, Jason; Bhiman, Jinal; Schramm, Chaim; Vu, Ashley; Law, William; Zhang, Baoshan; Bekker, Valerie; Abdool Karim, Salim; Ippolito, Gregory; Morris, Lynn; et al.
Abstract The developmental pathways of broadly neutralizing antibodies (bNAbs) against HIV are of great importance for the design of immunogens that can elicit protective responses. Here we show the maturation features of the HIV-neutralizing anti-V1V2 VRC26 lineage by simultaneously sequencing the exon together with the downstream intron of VRC26 members. Using the mutational landscapes of both segments and the selection-free nature of the intron region, we identify multiple events of amino acid mutational convergence in the complementarity-determining region 3 (CDR3) of VRC26 members, and determine potential intermediates with diverse CDR3s to a late stage bNAb from 2 years prior to its isolation. Moreover, we functionally characterize the earliest neutralizing intermediates with critical CDR3 mutations, with some emerging only 14 weeks after initial lineage detection and containing only ~6% V gene mutations. Our results thus underscore the utility of analyzing exons and introns simultaneously for studying antibody maturation and repertoire selection. Knowledge on how antibody responses have evolved is critical for the induction of protective immunity. Here the authors analyse, using high-throughput sequencing of both exon and intron regions, the mutation and lineage development of an HIV-neutralizing antibody to find an unexpected early emergence of broadly neutralizing species.